Initial Preparation and Characterization of Single Step Fabricated Intermediate Temperature Solid Oxide Fuel Cells (IT‐SOFC)1. Issue 3 (31st October 2013) - Sivasankaran, V.; Combemale, L.; Pera, M. C.; Caboche, G.; Steiner, Nadia; Hissel, Daniel; Bultel, Yann
Abstract In this study, facile tape casting process has been successfully carried out to fabricate an unit anode supported intermediate temperature solid oxide fuel cell (IT‐SOFC) with four different layers: a composite cathode which is a mix of La0.6Sr0.4Co0.2Fe0.8O3 (LSCF48) and Gd0.1Ce0.9O1.9 (GDC10), GDC10 as thin electrolyte layer, NiO‐GDC10 without pore former as thin anode functional layer (AFL), and anode support layer of NiO‐GDC10 with carbon pore former. The multi‐layer was sintered once to produce an unit planar cell. An OCV of 1.002 V at 500 °C, and maximum power density of 466 mW cm–2 at 648 °C are obtained. These results indicate negligible leakage of fuel through electrolyte. Furthermore scanning electron microscope (SEM) revealed crack free dense electrolyte. The single step sintering process gives an unit planar cell, which exhibits good performance without use of sintering aids, co‐pressing, and lamination of green tape.